Cooperatives' social responsibility in crisis time: how should they behave? - Cristina Aragón Amonarriz (AECOOP Escuela de Estudios Cooperativos, 2016)
Proactive Social Responsibility (PSR) plays a relevant role building competitive advantage and supporting organizational success in cooperatives. It is particularly desirable and challenging in recession periods. This paper studies how economic crisis impacts in different levels of cooperatives, and it aims to identify how PSR can be restored. In order to explore the organizational behaviour, the case study approach was selected to analyse three manufacturing cooperatives located in the Basque Country (Spain). The paper identifies three sources of hinders of PSR in cooperative context and it proposes two conditions to develop PSR. The originality of the paper relies on pushing the research of the organizations’ responsibility face to the crisis periods, diving into the cooperatives black box to catch the problems hindering their PSR, and proposing PSR leverages in cooperatives.